Prosedur pemeriksaan lopografi kombinasi colon in loop pada klinis post ileustomi di instalasi radiologi RS PKU muhammadiyah gamping - Vinka Aulia Nur Islami; Muhammad Za’im (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
The digestive system is a series of organs functioning in the processes of intake, digestion, nutrient absorption, and metabolic waste excretion. The large intestine, as a vital part of the digestive system, plays a crucial role in water absorption and fecal formation. Disorders of the large intestine, such as ileus, can obstruct the movement of gastrointestinal contents, necessitating medical intervention, including ileostomy procedures. Lopography or barium enema, is a radiological examination used to evaluate the large intestine using contrast media inserted via a catheter trough the stoma. The contrast medium used is barium sulfate, administered trough the proximal stoma, distal stoma, and the anus. This study exmploys a qualitative method with a case study approach. It aims to determine the procedure for combined lopography and colon in loop examination in post ileustomi clinical cases. Data collection was conducted from September 2025 to April 2026 through observastion, interviews, and documentation. Data analysis included data reduction, data presentation, and conclusion drawing. The result indicated that specific preparations were required prior to the examination, using 150 g of barium sulfate dissolved in 1.000 ml of water as the contrast medium. The projections used were plain AP, AP post contrast, RPO, and lateral. post evacuation imaging was not performed as the required diagnostic information was deemed sufficient. Furthermore, this decision considered patient comfort, time efficiency, and the minimization of unnecessary radiation exposure to the patient